2015
DOI: 10.3233/jae-140006
|View full text |Cite
|
Sign up to set email alerts
|

Limiting factors of the response time of the magnetorheological damper

Abstract: Magnetorheological dampers seem to be suitable for the adaptive car suspension systems. For proper operation of the semi-active algorithms (skyhook, groundhook), the force response of the damper must be fast enough. In this paper, the response time of the Delphi vehicle MR damper is examined and the sources of the overall force time response on the control voltage are discussed. One of the main sources of the response time seems to be electro-magnetic circuit of the MR damper. A principle of an optimal control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 16 publications
0
25
0
Order By: Relevance
“…Therefore pressure lags in the above piston chamber due to the fluid stream through the base valve may occur; to avoid that phenomenon damping forces should be tuned [40]. Moreover, the time response of a MR damper could be limited by eddy currents in the coil's core, so an optimal design of the controller is often needed [41,42].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore pressure lags in the above piston chamber due to the fluid stream through the base valve may occur; to avoid that phenomenon damping forces should be tuned [40]. Moreover, the time response of a MR damper could be limited by eddy currents in the coil's core, so an optimal design of the controller is often needed [41,42].…”
Section: Introductionmentioning
confidence: 99%
“…For response measurement, a patented current controller developed by our team was used instead of the common power supply. The controller drives the rise and drop of the current using the overvoltage technique described in [ 36 , 37 ]. The controller is supplied by a voltage of 30 V and the input signal is generated from a control computer.…”
Section: Methodsmentioning
confidence: 99%
“…Koo et al [ 35 ] measured the transient response of the LORD Motion Master automotive damper. The overall response time of the damper was identified in the range of 15–55 ms. Based on the previous study, Strecker et al [ 36 ] defined three main sources which prolong the response time: (i) MRF, (ii) electrical circuit—especially the coil inductance, and (iii) magnetic circuit. Subsequently, they designed a special current controller, minimizing the response time of the electrical circuit when switching on and also switching off [ 37 ] with the overvoltage method.…”
Section: Introductionmentioning
confidence: 99%
“…Effectively, the actuator dynamics of MR dampers is severely degraded. Specifically, the experiments by Strecker et al (2015) as well as Zheng et al (2015) showed again that the electromagnetic circuit plays a significant role in the eddy current–induced time delay. For example, Zheng et al (2015) designed a correcting circuit in order to accelerate the damper behavior.…”
Section: Introductionmentioning
confidence: 93%